Oral hygiene education of special needs children. Part 1: children with autism spectrum disorder. Issue 1 (1st January 2019) - Doichinova, Lilia; Gateva, Natalia; Hristov, Krasimir
Abstract: The purpose of this study was to implement an educational programme for oral hygiene of children with autism. It involved 30 children with autism aged 6–11 years. For their training, Picture Exchange Communication System (PECS) images for oral hygiene and tooth-brushing techniques were made. The oral hygiene level was assessed using the Silness & Löe Oral Hygiene Index. The children had poor oral hygiene due to hindered communication and motivation. The practical training of the children with autism included in the study lasted one year and was performed with the help of their parents. At the end of the one-year educational programme in oral hygiene, there was improvement in the oral hygiene habits of the children. The PECS images helped to improve the communication and the oral hygiene habits in the children with autism.